2018
DOI: 10.1111/ajd.12910
|View full text |Cite
|
Sign up to set email alerts
|

Severe cutaneous eruptions following the topical use of preparations containing bufexamac: Is it time to reconsider its registration in Australia?

Abstract: Despite being a well-recognised cause of allergic contact dermatitis with an embargo in many countries around the world, bufexamac is available over the counter in topical preparations in Australia. We present a series of patients who developed severe cutaneous eruptions after the topical application of bufexamac containing preparations to highlight the potential risks of this medication, as well as advocate for the reconsideration of its registration by the Therapeutic Goods Administration in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Currently, it is not available in New Zealand, Japan, the European Union, the USA or Canada. Various Australian pharmaceutical companies do not produce bufexamac anymore, although it is still available in that country 42 . Therefore, the role of bufexamac in SAD may decrease considerably.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is not available in New Zealand, Japan, the European Union, the USA or Canada. Various Australian pharmaceutical companies do not produce bufexamac anymore, although it is still available in that country 42 . Therefore, the role of bufexamac in SAD may decrease considerably.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 2%–4% of emergency department (ED) presentations in Australia result from dermatological conditions, with the majority being triaged as low urgency 3,4 . The now‐banned topical anti‐inflammatory bufexamac had caused several cases of severe ACD leading to hospitalization, and this had highlighted the dearth of information of the causes of severe ACD presenting to EDs 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…3,4 The now-banned topical anti-inflammatory bufexamac had caused several cases of severe ACD leading to hospitalization, and this had highlighted the dearth of information of the causes of severe ACD presenting to EDs. 5,6 The aim of this study was to identify cases of ACD presenting to EDs in a large Australian city, with emphasis on the causes of severe and acute cases of ACD, and their management. The mean age of patients was 37 years (range 0-87), and females accounted for 47.4% (108/228).…”
Section: Introductionmentioning
confidence: 99%